PRODUCT DEVELOPMENT STRATEGY IN MSME DEFIA OYSTER MUSHROOM IN JAMBI - Raja Sarah Fatricia; Dessy Elliyana (Journal of Business Studies and Management Review, 2019)
Micro Small Medium Enterprises (MSME) gives the latest innovation to the development of its business. Enterprises in order to maintain their survival in order to survive in a competitive climate should have a strategy to attract consumers to switch to their products. One strategy to choose from is product development strategy. So the purpose of this research is to know the internal and external conditions of MSMEs Nugget Oyster Defia in determining product development strategy and analyze and recommend product development strategy based on SWOT analysis to MSME Nugget Oyster Defia. This research was conducted at MSME Nugget Oyster Defia fungus located in Jambi City. Data collection using secondary and primary data.The method of data collection by using observation and direct interview which result will be processed using IFE, EFE and SWOT matrix. Based on the results of the analysis obtained IFE matrix which shows a score of 2.802 score that identified wide space and business improvement and EFE matrix with a score of 2.6255 shows nugget business can be said to be successful and able to attract profits. In the IFE and EFE matrix, the SWOT analysis is to increase the number of outputs and business performance inputs, expand marketing area and increase promotion, increase the number of experts and cooperation, use good technology and planning system, improve nugget business quality and cooperate with other agencies to development